Self-Refinement Loops in CodeGen-2B: Diminishing Accuracy Gains Beyond Three Iterations - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: Does applying self-refinement loops to codegen-2b yield diminishing returns in accuracy improvement after three iterations on the APPS competition-level dataset. 14 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.5/10. This report is a machine-generated literature syn
Machine-generated literature synthesis.